PERAN GURU DALAM PENCEGAHAN BULLYING DI LINGKUNGAN SEKOLAH MI NWDI 05 PANCOR - Siti Solihah; Marudin; Siti Zainab Muslimin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Bullying is a serious problem in educational settings that disrupts students’ psychological development and the school learning climate. Teachers play a crucial role in preventing such aggressive behavior. This study aims to describe teachers’ roles in preventing bullying and to identify the forms of bullying occurring at MI NWDI 05 Pancor. Using a qualitative descriptive approach, data were collected from the principal, islamic teacher and homeroom teachers (grades 3A, 4A, and 6B) through interviews, observation, and documentation. The data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that the dominant forms of bullying include verbal bullying (mocking physical appearance and parents’ names), mild physical bullying (hitting and seizing belongings), and social bullying (exclusion). Teachers perform three main functions: (1) as educators and instructors who integrate anti-bullying values into lessons; (2) as guides and mediators who resolve student conflicts; and (3) as caregivers providing emotional support and counseling to victims. Although teachers have taken individual actions, the school lacks a formal anti-bullying program. Therefore, stronger collaboration among teachers, school leaders, and parents is needed to establish a safe, inclusive, and bullying-free school environment. Bullying is a serious problem in educational settings that disrupts students’ psychological development and the school learning climate. Teachers play a crucial role in preventing such aggressive behavior. This study aims to describe teachers’ roles in preventing bullying and to identify the forms of bullying occurring at MI NWDI 05 Pancor. Using a qualitative descriptive approach, data were collected from the principal, islamic teacher and homeroom teachers (grades 3A, 4A, and 6B) through interviews, observation, and documentation. The data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that the dominant forms of bullying include verbal bullying (mocking physical appearance and parents’ names), mild physical bullying (hitting and seizing belongings), and social bullying (exclusion). Teachers perform three main functions: (1) as educators and instructors who integrate anti-bullying values into lessons; (2) as guides and mediators who resolve student conflicts; and (3) as caregivers providing emotional support and counseling to victims. Although teachers have taken individual actions, the school lacks a formal anti-bullying program. Therefore, stronger collaboration among teachers, school leaders, and parents is needed to establish a safe, inclusive, and bullying-free school environment.